Early readmissions of spontaneous bacterial peritonitis in the USA: Insights into an emerging challenge. Issue 11 (31st July 2022) - Dahiya, Dushyant Singh; Sanaka, Madhusudhan R; Kichloo, Asim; Singh, Amandeep; Wachala, Jennifer; Perisetti, Abhilash; Goyal, Hemant; Garg, Rajat; Shaka, Hafeez; Pisipati, Sailaja; Inamdar, Sumant; Al‐Haddad, Mohammad
Abstract: Background and Aim: Early readmissions of spontaneous bacterial peritonitis (SBP) are often associated with poor outcomes. We compared characteristics and outcomes for index and 30‐day readmissions of SBP in the USA. Methods: We analyzed the Nationwide Readmissions Database for 2018 to identify all adult (≥ 18 years) 30‐day readmissions of SBP in the USA. Hospitalization characteristics and outcomes for index and 30‐day readmissions of SBP were compared. Independent predictors of 30‐day readmissions were also identified. Results: In 2018, of the 5, 797 index admissions for SBP, 30% (1726) were readmitted within 30 day. At the time of readmission, the most common admitting diagnosis was alcoholic cirrhosis of the liver with ascites (11.8%) followed by sepsis due to an unspecified organism (9.2%). SBP as an admitting diagnosis was identified for only 8.3% of these 30‐day readmissions. Compared with index admissions, 30‐day readmissions of SBP had a lower mean age (56.1 vs 58.6 years, P  < 0.001) without a statistically significant difference for gender. Furthermore, 30‐day readmissions of SBP were associated with significantly higher odds of inpatient mortality (10% vs 4.9%, OR: 2.15, 95% CI: 1.66–2.79, P  < 0.001), and mean total hospital charge ($85, 031 vs $56, 000, mean difference: 29, 032, 95% CI: 12, 867–45, 197, P  < 0.001) compared with index admissions. The presence of chronic pulmonary disease, liver failure, inpatient dialysis, and discharge against medical advice were identified as independent predictors for increased 30‐day readmissions of SBP. Conclusion: The 30‐day readmission rate of SBP was 30% and these readmissions were associated with higher odds of inpatient mortality compared with index admissions.